How default effects and decision timing affect annuity uptake and health consciousness - Franziska Unger; Martina Steul-Fischer; Nadine Gatzert (The Geneva Papers on Risk and Insurance - Issues and Practice, 2022)
Annuities provide a lifelong income stream and can therefore help individuals to mitigate the risk of outliving their savings, a highly topical issue in the context of increasing life expectancies. Given that real-world annuitization rates remain relatively low, we investigate the influence of behavioral biases on people's choice between a lifelong annuity and a lump sum payout. In so doing, we focus on the impact of default effects due to a preselected annuity option (default option) and the impact of the decision's timing (decisions on annuitization taken by younger individuals refer to a distant future, those taken by older individuals to a near future) on annuity uptake and health consciousness. We used a scientific survey panel to conduct an online experiment with a diversified sample of 339 participants (55.2% female, average age0.167em=0.167em42.5~years). Our results show that the timing of the decision moderates the default effect on annuity uptake, in that the effect of a preselected (default) annuity option is stronger for distant-future decisions (i.e., choice of annuity instead of lump sum at retirement made by younger participants purchasing a deferred annuity) than for near-future decisions made by older individuals who are closer to retirement. We further find that the default effect moderates health consciousness after choosing an annuity. Health consciousness is stronger in the no-default condition than in the annuity default condition.
Keywords: 330; Default effect; Decision timing; Annuity uptake; Health consciousness; Online experiment